Female slave vs female slave: ʼmh and s pḥh in the HB - Bridge, Edward J. (The journal of Hebrew scriptures, 2012)
This study of אָמָה and שִׁפְחָה shows that there is no inherent distinction in meaning between the two terms, due to the intertwining of context of use and text genre. Both are used for slave wives in Genesis, in legislation contexts, in deferential language by women, in property lists, and in relation to the master or mistress. Yet patterns of use occur. אָמָה predominates in legislation and marriage contexts; and שִׁפְחָה predominates in Genesis and when generally designating female slaves.